Predation of threespine stickleback (Gasterosteus aculeatus) on the eggs of Atlantic herring (Clupea harengus) in a Baltic Sea lagoon. (24th March 2014) - Kotterba, Paul; Kühn, Carsten; Hammer, Cornelius; Polte, Patrick
Abstract : We analyzed the predation of threespine stickleback ( Gasterosteus aculeatus ) on the spawn of Atlantic herring ( Clupea harengus ) in a mesohaline lagoon of the Baltic Sea, hypothesizing a significant predation effect of a resident estuarine fish on the recruitment of an anadromous oceanic species. A predator exclusion field experiment using artificially spawned experimental units was combined with tank feeding experiments to estimate the effects of temperature and prey density on the herring egg consumption by estuarine G. aculeatus . The predator exclusion experiment showed a significant mortality of herring eggs caused by estuarine predatory fish species. A strong increase in the consumption of herring eggs by sticklebacks was observed between 11°C and 15°C (Q10 = 3.15). Additionally, we found a significant positive correlation between egg concentration per area and predation intensity. Nearly all eggs were consumed at concentrations ≥ 25 eggs cm −2, but predation was less intense at egg concentrations below that threshold. Field data on herring egg concentrations, stickleback abundances, and stomach contents were combined with the findings of the experiments to estimate the percentage of spawned herring eggs that is consumed by the local stickleback (MPS ). The highest MPS (11.4%) was estimated for a week in April in the second half of the spawning season. We conclude that stickleback predation on herring eggs potentially affects the local herring year class strength.